Training on School Management Health Diagnostics Using the SIDIKMAS-BRO Application - Sururi, Sururi; Triatna, Cepi; Permana, Johar; Rahyasih, Yayah; Kadarsah, Deni (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: Effective school leadership is a key determinant of educational quality and student outcomes. In Indonesia, the School Transformation Program, initiated by the Ministry of Education, aims to accelerate school improvement by strengthening the role of principals and promoting the Pancasila Student Profile. Contribution: This study contributes to the body of knowledge on digital transformation in school leadership by introducing and evaluating the SIDIKMAS-BRO application as a localized, user-friendly diagnostic tool. Method: The training was implemented as a community service activity at SMPN 1 Pelabuhan Ratu, involving 35 school leaders. Participants engaged in panel discussions, interactive sessions, and hands-on practice using the SIDIKMAS-BRO application to assess school planning, leadership, and instructional supervision. Results: The training enhanced participants’ understanding of data-driven school diagnostics. They demonstrated improved ability to use the application to evaluate key management areas and identify institutional strengths and weakness. Conclusion: The program effectively strengthened the capacity of school leaders to utilize digital diagnostic tools. It contributed to promoting collaborative, evidence-based decision-making for school improvement.